Efeitos do uso de taninos sobre a digestibilidade dos componentes nutricionais de alimentos proteicos e volumosos - Mundim, Adrielle Torres (2019)
Tannins are natural additives that can bind to proteins, metal ions, and polysaccharides modifying the rumen fermentation. In vitro and in situ experiments were performed with the objective of evaluating the effects of a tannin blend on in vitro digestibility of dry matter, crude protein and neutral detergent fiber (IVDMD, IVCPD e IVNDFD, respectively) and in situ digestibility of dry matter, crude protein and neutral detergent fiber (ISDMD, ISCPD e ISNDFD, respectively) of proteins and fibrous feeds. The substrates were composed of seven protein feeds: corn dried distillers grains (DDG), corn wet distillers grains (WDG), xylose- treated soybean meal (soy pass® ), soybean meal, sunflower meal, cottonseed meal, cottonseed cake, and five fibrous feeds: Urochloa brizantha cv. Marandu (samples from the rainy and dry season), Panicum maximum cv. Tanzânia, corn silage and Tyfton-85 bermuda grass (Cynodon sp) hay. Four bulls Nellore cannulated in the rumen, with average body weight of 578±37 kg and 27 months of age grazing Marandu grass were used. The treatments consisted of the inclusion or not of tannins to the supplements of the animals, which two of the four animals received supplementation with tannin (1g kg-1 DM), composed of 76% of condensed (Extract of Quebracho - Schinopsi lorentzii) and hydrolysed (Castanea spp) tannins; and two animals received supplementation without inclusion tannin. The ruminal fluid was collected separately from each animal and the gas production (GP) recorded at 6, 12 e 24 h of incubation. In vitro digestibility and concentration of ammoniacal nitrogen (N-NH3) were measured at 24 h of incubation. The in situ digestibility was measured at 0, 2, 4, 8, 12, 24, 48, 72 and 96 h, which the residues were estimated for potentially degradable fraction (B), digestion rate [kd (h −1 )] and undigested fraction (U). The model that presented the best fit to the in situ data was chosen based on Akaike information criterion (AICc) and for each parameter of the model, the 95% confidence interval was estimated. Addition of tannin reduced (P<0.05) the IVCPD of the soybean meal. In contrast, there was no effect of tannin supplementation on (P>0.05) the GP, N-NH3, IVDMD and IVNDFD of evaluated feeds. Tannin supplementation reduced the parameter B and increased the fraction U of ISDMD and ISCPD of cottonseed meal. There was an increase in the parameter kd (h −1 ) for ISDMD of soybean meal, Marandu grass (dry season) and reduction for corn silage. Additionally, the inclusion of tannins promoted an increase in the parameters U and kd (h −1 ) for ISCPD of soybean meal. The effects of the blend of tannins were not the same for in vitro and in situ, but the dose administration of the 1 g kg-1 provided a reduction in the digestibility of dry matter and crude protein, and did not reduce the digestibility of neutral detergent fiber and ruminal ammoniacal nitrogen.